PERAN GURU PENDIDIKAN AGAMA ISLAM DALAM MEMBENTUK KARAKTER PESERTA DIDIK DI SMPI INTEGRAL LUQMAN AL-HAKIM 02 - Zainal Arifin (UNISAN JURNAL, 2024)
: The aim of this research is to find out and understand the role of Islamic Religious Education Teachers in increasing students’ interest in learning in Islamic Religious Education subjects. This research used qualitative research methods, taking place at SMPI Integral Luqman Al-Hakim 02. Researchers conducted structured interviews and unstructured interviews with resource persons (SMPIT Islamic Religious Education teachers) supported by documentation data and direct observation. The findings in this research, there is a special role regarding the review of the role of teachers in increasing students’ interest in learning in PAI subjects at SMPI Integral Luqman Al-Hakim 02, it can be concluded that apart from these three roles, namely teachers as educators, trainers and supervisors, teachers also play a role. The models and mentors carried out prove that the role of teachers is very influential in increasing students’ interest in learning PAI, at SMPI Integral Luqman Al-Hakim 02. This school runs 2 (two) curricula, namely the general curriculum and the special curriculum (Islamic/religious activities, daily religious practices such as ablution, dhuha prayer, muroja’ah memorization, midday prayers in congregation, and the call to prayer, but students still have an interest in learning PAI well. This means that if the teacher’s role is carried out well it can influence students’ interest in learning PAI despite the content. The material has been improved, so it is necessary to add additional PAI study time to PAI school hours, especially at SMPI Integral Luqman Al-Hakim 02